The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fonc.2018.00589
|View full text |Cite
|
Sign up to set email alerts
|

The Use of HPV16-E5, EGFR, and pEGFR as Prognostic Biomarkers for Oropharyngeal Cancer Patients

Abstract: Background: Anti-epidermal-growth-factor-receptor (EGFR) therapies in combination with radiotherapy are being studied on de-escalation clinical trials for HPV-related oropharyngeal cancer (OPC) patients. The HPV16-E5 oncoprotein increases recycling of activated EGFR to the cell surface, enhancing factor signal transduction. Our aim was to evaluate viral HPV16-E5 oncogene expression as well as EGFR and phosphorylated-EGFR (pEGFR), protein levels as biomarkers for clinical outcome in a retrospective cohort of OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Nevertheless, our results are in overall agreement with published data with the overwhelming belief that p16-positive HNSCC have improved locoregional tumor control and survival with conventional therapy [21,27,41]. Potential future refinement could be brought about by including the copy number variation of the CDKN2A gene that encodes p16ink4a [42], and involving other related prognostic biomarkers such as epidermal growth factor receptor (EGFR), and key transcription factors as molecular signature of HPV presence [19,43], especially for de-escalation of radiotherapy combined with anti-EGFR receptor treatment [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results are in overall agreement with published data with the overwhelming belief that p16-positive HNSCC have improved locoregional tumor control and survival with conventional therapy [21,27,41]. Potential future refinement could be brought about by including the copy number variation of the CDKN2A gene that encodes p16ink4a [42], and involving other related prognostic biomarkers such as epidermal growth factor receptor (EGFR), and key transcription factors as molecular signature of HPV presence [19,43], especially for de-escalation of radiotherapy combined with anti-EGFR receptor treatment [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in transgenic mice suggested that the expression of HPV-16 E5 in stratified squamous epithelia led to a higher frequency of spontaneous skin tumours [ 109 ] and caused cervical cancer when a prolonged oestrogen treatment was given [ 109 , 110 ]. As discussed earlier, upon integration of the HPV genome in high-risk HPV-18, E5 is often disrupted; however, in the case of HPV-16-positive cervical and oropharyngeal cancers, the expression of E5 is more likely and has been shown to be detectable [ 111 , 112 , 113 , 114 , 115 ], suggesting that E5 may contribute to malignant progression of the cancer.…”
Section: Carcinogenic Orchestration By E5 E6 and E7mentioning
confidence: 99%
“…On the other hand, the presence of E5 viral transcripts could be a major marker of active viral infection, and subsequently a target of immunotherapy. HPV16 E5 was highly expressed in HPV16-positive oropharyngeal cancer (OPC) patients (Taberna et al 2018). Generally, most studies have focused on E7 oncoprotein, because it is more abundantly expressed and better characterized immunologically.…”
Section: Discussionmentioning
confidence: 99%